Electric Drive System of Domestic A Type Additional Metro Trainsfor Guangzhou Metro - HE Hong-cheng; LIAO Yun (机车电传动)
Basic parameters and performance requirement of Guangzhou metro domestic A type additional metro trains electric drive system were introduced. Design idea and technology details of the electric drive system’s traction/electrical brake characteristic, main circuit,and train traction control system were explained, as well as compared with the Siemens trains served in the same lines. Guangzhou metro domestic A type additional metro trains and their electric drive systems had passed the type test and operation appraisal, and now the trains are served in Guangzhou metro line 2 with good operation situation.